Determinants of depressive symptoms among postpartum mothers: a cross-sectional study in Ethiopia. Issue 9 (13th September 2022) - Anato, Anchamo; Baye, Kaleab; Stoecker, Barbara
Abstract : Objective: This study aims to assess the determinants of depressive symptoms among postpartum mothers. Design: A community-based cross-sectional study was conducted. Setting: Ten randomly selected rural kebele s of Meket district of Ethiopia. Participants: A random sample of 232 mothers with infants 5–10 months was included in this study. Data analysis: Forward multivariable logistic regression analysis. Results: The factors significantly associated with increased odds of maternal postpartum depressive symptoms were: moderate (adjusted OR (AOR) 4.44, 95% CI 1.34 to 14.72) and severe (AOR 12.98, 95% CI 5.24 to 32.14) household food insecurity; infant underweight (AOR 2.99, 95% CI: 1.21 to 7.37) and infant acute respiratory infection (ARI) (AOR 7.0, 95% CI: 3.09 to 15.99). Maternal education, workload and age, household socioeconomic status, distance to the health facility, and child stunting, diarrhoea and fever were not significantly associated with postpartum depressive symptoms in adjusted logistic regression. Conclusion: Household food insecurity, infant ARI and infant underweight had significant associations with postpartum depressive symptoms. Therefore, interventions that address infant nutrition and health and household food insecurity within the framework of the productive safety net programmes (PSNPs) as well as programmes focused on preventing, detecting and solving maternal mental health challenges may be helpful to improve maternal mental well-being and promote graduation from the PSNP.